2017
DOI: 10.1016/j.gore.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent atypical polypoid adenomyoma and pregnancy: A new conservative approach with levonorgestrel-releasing intrauterine system

Abstract: HighlightsLevonorgestrel IUD was effective in treatment of recurrent APA.No side effects were reported.No impairments on a subsequent pregnancy were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…We hypothesized that the progesterone released from the LNG‐IUS would be able to clear the hypothetical microscopic residual tumor. There is a previous case report of LNG‐IUS usage for recurrent APA, suggesting the effectiveness of the LNG‐IUS for treatment of recurrent APA patients who want to preserve fertility . As in our case, it may be useful when there is a possibility of microscopic residual tumor following primary treatment.…”
Section: Discussionsupporting
confidence: 55%
“…We hypothesized that the progesterone released from the LNG‐IUS would be able to clear the hypothetical microscopic residual tumor. There is a previous case report of LNG‐IUS usage for recurrent APA, suggesting the effectiveness of the LNG‐IUS for treatment of recurrent APA patients who want to preserve fertility . As in our case, it may be useful when there is a possibility of microscopic residual tumor following primary treatment.…”
Section: Discussionsupporting
confidence: 55%
“…There is a previous report of recurrent APAM treated with high-dose medroxyprogesterone acetate (MPA) followed by maintenance therapy with dienogest [8]. Another study reported a case of recurrent APAM in a patient with and adjuvant progestin-releasing intrauterine device, who later delivered a baby [9]. Although it is a proof-of-concept that the usual-dose progestin can treat APAM, a benign, ER-positive, progesterone receptor-positive tumor related to unopposed estrogen [3,10], some other authors prefer highdose MPA for maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In post-menopausal women, hysterectomy is often considered the preferred treatment for atypical polypoid adenomyoma (APAM). However, for patients who wish to retain their fertility potential, a more conservative surgical approach is typically recommended [17].…”
Section: Treatmentmentioning
confidence: 99%
“…Additionally, the use of a levonorgestrel intrauterine device (IUD) has been suggested as a form of maintenance therapy for young women who wish to preserve their fertility [17].…”
Section: Treatmentmentioning
confidence: 99%